2023
DOI: 10.1002/adma.202302868
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Based 3D Printing of Complex‐Shaped Photonic Colloidal Glasses

Abstract: Colloidal glasses display angle‐independent structural color that is tunable by the size and local arrangement of submicron particles. While films, droplets and microcapsules with isotropic structural color have been demonstrated, the shaping of colloidal glasses in three dimensions remains an open manufacturing challenge. Here, we report a light‐based printing platform for the shaping of colloidal glasses into three‐dimensional objects featuring complex geometries and vivid structural color after thermal trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 58 publications
(90 reference statements)
0
7
0
Order By: Relevance
“…Inspired by natural amorphous PhC structures, scientists have developed methods such as spray coating, layer‐by‐layer deposition, and phase separation to create short‐range‐ordered amorphous PhCs. [ 98–104 ] These PhC structures can change color by varying lattice spacing and refractive index under external stimuli. Lee et al developed angle‐independent photonic pixels that can change with voltage (Figure 6A).…”
Section: Amorphous Phcs Displaymentioning
confidence: 99%
“…Inspired by natural amorphous PhC structures, scientists have developed methods such as spray coating, layer‐by‐layer deposition, and phase separation to create short‐range‐ordered amorphous PhCs. [ 98–104 ] These PhC structures can change color by varying lattice spacing and refractive index under external stimuli. Lee et al developed angle‐independent photonic pixels that can change with voltage (Figure 6A).…”
Section: Amorphous Phcs Displaymentioning
confidence: 99%
“…Recently, three-dimensional printing has been used as an effective way to manufacture such materials. 38–44…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Meanwhile, the AM of ceramic-based spherical particles requires the incorporation of large amounts of template particles in a binder system and may lack mechanical integrity, when consisting of loose ceramic particles. 21,22 Regardless of the shaping method, the application as structural color requires that the structure contains features' sizes with a narrow variation and in the range of the wavelength of interest, i.e., nanometer to sub-micrometer, precisely distributed in the 3D macroscale. A study by Zhou et al 23 demonstrated the possibility to generate ceramic-based photonic structures utilizing preceramic polymers as starting material and performing subsequent pyrolysis to form polymerderived porous ceramics.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although several research groups have already applied AM to produce complex ceramic structures from preceramic polymers, , the investigation of AM of structural colors using preceramic polymers remains unexplored. Instead, other strategies to print structural colors have been studied, but they were often polymer based, thus lacking UV resistance and being prone to deformation under moderate temperatures. , Meanwhile, the AM of ceramic-based spherical particles requires the incorporation of large amounts of template particles in a binder system and may lack mechanical integrity, when consisting of loose ceramic particles. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation